2018
DOI: 10.3390/chemengineering2030029
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hematite and Siderite as Heterogeneous Catalysts for an Effective Degradation of 4-Chlorophenol via Photo-Fenton Process

Abstract: This paper describes a simple and low-cost process for the degradation of 4-Chlorophenol (4-CP) from aqueous solution, using natural Tunisian Hematite (M 1 ) and Siderite (M 2 ). Two natural samples were collected in the outcroppings of the Djerissa mining site (Kef district, northwestern Tunisia). Both Hematite and Siderite ferrous samples were characterized using several techniques, including X-Ray Diffraction (XRD), Nitrogen Physisorption (BET), Infrared Spectroscopy (FTIR), H 2 -Temperature Programmed Redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Use of the siderite catalyst gave 100% conversion of 4-CP and 54% TOC removal. In terms of the removal of several organic compounds in an aqueous condition, the work confirmed that natural materials can be used as catalysts [60]. Wei et al used siderite (doped with Mn and Ce) for the selective catalytic reduction (SCR) of NO x by NH 3 .…”
Section: Introductionmentioning
confidence: 86%
“…Use of the siderite catalyst gave 100% conversion of 4-CP and 54% TOC removal. In terms of the removal of several organic compounds in an aqueous condition, the work confirmed that natural materials can be used as catalysts [60]. Wei et al used siderite (doped with Mn and Ce) for the selective catalytic reduction (SCR) of NO x by NH 3 .…”
Section: Introductionmentioning
confidence: 86%
“…The photo-Fenton reaction has been described by many authors as one of the most promising ways to remove highly hazardous organic species. In this special issue, natural Tunisian materials containing very important amounts of iron were reported as catalysts for an effective degradation of 4-Chlorophenol via the photo-Fenton process in a contribution by Bel Hadjltaief, Elena Gálvez et al The Negligible metal leaching and catalyst reutilization results without any loss of activity confirmed a remarkable catalytic stability of natural catalysts, opening a new window in the materials field for this application [19].…”
mentioning
confidence: 93%
“…Both strategies pose numerous technical difficulties when applied in practice; therefore, iron-based heterogeneous cocatalysts are gaining interest. Among them are Fe 0 (metallic iron, zero-valent iron, ZVI), Fe 2 O 3 (hematite), and Fe 3 O 4 (magnetite) [28][29][30][31]. Oxides act through coordinating surface sites of Fe 2+ that form complexes with contaminants and reduce them [28].…”
Section: Introductionmentioning
confidence: 99%